Navigating support and accountability: exploring academic supervision and its impact on school teacher performance - Ika Pratiwi; Ahmad Iswanto (UHAMKA Press, 2026)
Purpose: This study investigates how academic supervision impacts school teacher performance by balancing developmental support with administrative accountability, mediated by teacher self-efficacy. Method: A convergent parallel mixed-methods design was employed with N = 320 teachers and n = 24 supervisors. Quantitative survey data were analyzed using SEM and bootstrap mediation, while qualitative interview data were analyzed through thematic coding in NVivo. Findings: High support and accountability yielded the highest performance (M = 4.45). SEM confirmed developmental support (β = 0.38) and accountability (β = 0.19) predict performance, mediated by self-efficacy (Indirect Effect = 0.12). Qualitatively, constructive dialogue fostered high engagement (62%), whereas directive or punitive monitoring induced surface compliance (26%) or resistance (12%). Practical implications: Supervisors should scaffold accountability with continuous support to build teacher efficacy. Practices must shift from top-down inspection to collaborative coaching, using bi-directional feedback to enhance classroom delivery and alleviate teaching anxiety. Originality/value: This study offers a mixed-methods examination of teacher supervision, demonstrating how balancing support and accountability directly strengthens self-efficacy to drive instructional performance.